The Effectiveness of Telerehabilitation on Improving Knee Function in Patients with Osteoarthritis Knee: A Systematic Review and Meta Analysis - Yunita Rahayu Pratiwi; Suryo Saputra Perdana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Knee Osteoarthritis (KOA) is one of the leading causes of limitations in performing activities that impact in impaired knee function and mobility, necessitating physiotherapy intervention. Advancements in current technology have made it possible to receive treatment without the need for in-person meetings. This study aims to assess the feasibility of telehealth physiotherapy in improving knee function in OA patients. The design of study is Systematic Review and Meta-Analysis, with study sources obtained from Scopus, ProQuest, and PubMed databases using keywords based on the PICO framework. Data analysis was performed using Review Manager. The study identified a total of 1.726 articles, with a final screening resulting in 5 articles that were further examined. Each study had a Randomized Control Trials (RCT) research design and was oriented towards comparing telehealth with face-to-face interventions. Telerehabilitation did not show significant changes due to various factors, including the study's duration, physiotherapist supervision, patient motivation and adherence, as well as the comprehensiveness of exercise instructions.